1987
DOI: 10.1068/p160421
|View full text |Cite
|
Sign up to set email alerts
|

Letter Recognition at Low Contrast Levels: Effects of Letter Size

Abstract: Contrast variation was used to measure recognition thresholds for lowercase letters, with the aim of obtaining a better understanding of the role that early stages of visual processing play in letter recognition. Frequency-of-recognition curves were measured for alphabets of different letter size. Since variation of the adaptational state of the eye changes the characteristics of primary visual processing in a quantifiable way, recognition thresholds were measured both at a high (150 cd m-2) and at a low (0.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
3

Year Published

1990
1990
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
1
9
0
3
Order By: Relevance
“…Our finding that there was a trend for all children to make more errors as print size was reduced is consistent with the findings of Erdmann et al (1968) and Blommaert et al (1987), who showed that reducing print size makes words more difficult to read. But of greatest importance was the finding that only the children who failed the DT read differently as print size was reduced; they made more non-word errors.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that there was a trend for all children to make more errors as print size was reduced is consistent with the findings of Erdmann et al (1968) and Blommaert et al (1987), who showed that reducing print size makes words more difficult to read. But of greatest importance was the finding that only the children who failed the DT read differently as print size was reduced; they made more non-word errors.…”
Section: Discussionsupporting
confidence: 92%
“…This influence is small for the larger letter sizes (3 and 10 c deg −1 ) but is clearly more important for 20 c deg −1 and particularly for 30 c deg −1 letter sizes. This result was previously observed by Blommaert and Timmers (1987) and by Khanani et al. (2004) but they could not provide any information concerning the functional influence of surround luminance for each letter size (spatial frequency), because these two studies were performed with only two surround lighting conditions: non‐illuminated and illuminated surround.…”
Section: Discussionmentioning
confidence: 58%
“…Some previous experiments showed that an illuminated surround yielded contrast sensitivities higher than those obtained with a dark or an almost dark surround. Blommaert and Timmers (1987) performed an experiment with letters from 18 to 42 c deg −1 fundamental spatial frequency, but with only two observers, and found that an adapting field of 150 cd m −2 generated higher CS values than an adapting field of 0.9 cd m −2 . Cox et al.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing perceptual difficulty in decoding text should therefore help improve general reading ability. Erdman and Neal (1968) and Blommaert and Timmers (1987) both demonstrated that adults found it more difficult to recognise words and letters when the print size was reduced. Cornelissen, Bradley, Fowler and Stein (1991) report an increase in visuo-perceptual problems, in proportion to a decrease in spatial dimensions of text.…”
Section: Introductionmentioning
confidence: 97%